A case study of cracks in the scientific enterprise: Reinvention of information‐theoretic measures for graphs. (22nd April 2014) - Dehmer, Matthias; Mowshowitz, Abbe
Abstract : This article calls attention to flaws in the scientific enterprise, providing a case study of the lack of professionalism in published journal articles in a particular area of research, namely, network complexity. By offering details of a special case of poor scholarship, which is very likely indicative of a broader problem, the authors hope to stimulate editors and referees to greater vigilance, and to strengthen authors' resolve to take their professional responsibilities more seriously. © 2014 Wiley Periodicals, Inc. Complexity 21: 10–14, 2016